The shorter leg is 21cm, longer leg is 28 cm and hypotenuse is 35cm.
Step-by-step explanation:
Let,
The longer leg = x
The shorter leg = x-7
Hypotenuse = x+7
Using Pythagoras theorem;
![a^2+b^2=c^2\\(x-7)^2+(x)^2=(x+7)^2\\x^2-14x+49+x^2=x^2+14x+49\\2x^2-14x+49-x^2-14x-49=0\\x^2-28x=0\\x(x-28)=0\\](https://tex.z-dn.net/?f=a%5E2%2Bb%5E2%3Dc%5E2%5C%5C%28x-7%29%5E2%2B%28x%29%5E2%3D%28x%2B7%29%5E2%5C%5Cx%5E2-14x%2B49%2Bx%5E2%3Dx%5E2%2B14x%2B49%5C%5C2x%5E2-14x%2B49-x%5E2-14x-49%3D0%5C%5Cx%5E2-28x%3D0%5C%5Cx%28x-28%29%3D0%5C%5C)
Either,
x= 0
Or,
x-28=0 =>x=28
As length cannot be zero, therefore,
Longer side = 28cm
Shorter side = x-7 = 28-7 = 21cm
Hypotenuse = x+7 = 28+7 = 35cm
The shorter leg is 21cm, longer leg is 28 cm and hypotenuse is 35cm.
Keywords: triangle, pythagoras theorem
Learn more about triangles at:
#LearnwithBrainly
Answer:
11
Step-by-step explanation:
14-3 = 11
you have 14 apples and you eat 3 of them. wow! now you have 11 apples!
For 1 the equation of the parabola is y = x^2 - 8x + 3
For 2 the equation of the parabola is y = -2x^2 - 3x + 1
For 3 the equation of the parabola is y = -x^2 + 5x - 4